The Basic Empathy Scale in Chinese College Students: Adaptation and Psychometric Properties of a Revised Form - Chen, Yin; Dou, Guangbo; Chen, Liang (Frontiers in Psychology, 2021)
This study aimed to revise the Chinese version of the Basic Empathy Scale for college students. The cluster random sampling method was used to select 805 college students from two universities to conduct confirmatory factor analysis, correlation analysis, reliability analysis, and an independent samples t-test. The confirmatory factor analysis model illustrated that the two-factor model failed to fit the data, and the two-factor model with methodological effect was finally accepted. Therefore, the questionnaire exhibits a strong methodological effect among Chinese college students which requires further study. Emotional and cognitive empathy had a significant positive correlation with gratitude and Internet altruism behaviour, which showed good convergent validity. The gender difference test revealed that the emotional empathy level of girls was significantly higher than that of boys. The revised Basic Empathy Scale showed acceptable reliability and validity.